Direct interspecies electron transfer (DIET) can be suppressed under ammonia-stressed condition - reevaluate the role of conductive materials - Yan, Wangwang (2021)
Thermal hydrolysis pretreatment (THP) and anaerobic digestion (AD) integrated (THP-AD) process is a promising process for sludge management. However, the high ammonia production during the THP-AD process severely affects system's stability and performance. Conductive materials are widely reported to stimulate AD, thus they are potentially helpful in alleviating ammonia inhibition. This study investigated the effects of three widely studied conductive materials, i.e. zero-valent iron (ZVI), magnetite nanoparticles (Mag.) and powder activated carbon (PAC), on THP-AD process. Results showed that all the tested materials could effectively stimulate methanogenesis process under non-ammonia inhibition conditions. However, upon ammonia stress, these materials behaved distinctively with the best methanogenic performance in ZVI group followed by Mag. Group, and even worsened inhibition occurred in PAC group. The mechanisms behind were investigated from two levels-the reaction kinetics of each anaerobic digestion step and the responses of intracellular metabolism. It is revealed that ZVI effectively promoted all AD reactions, especially the energy unfavorable propanoate and butanoate metabolism and overall methanogenesis. In addition, ZVI likely acted as intracellular electron shuttles, and the conjunction point of ZVI to electron transfer system was identified as EtfAB: quinone oxidoreductase. On the contrary, the declined methanogenic performance in PAC group was attributed to selectively stimulated the growth of acetoclastic methanogen - Methanosaeta, which is sensitive to ammonia toxicity. The proteomic information further revealed that ammonia stress was unfavorable to the formation of direct interspecies electron transfer between syntrophic anaerobes. Overall, the present study provides fundamental knowledge about the role of different conductive materials in AD systems from intracellular proteomic level.